2015
DOI: 10.3171/2014.10.spine131126
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes and radiological findings and their correlation with each other after standard open discectomy for lumbar disc herniation

Abstract: OBJECT This retrospective study was designed to evaluate the clinical outcomes and radiological findings after open lumbar discectomy (OLD) in patients who were followed up for 10 years or longer. METHODS The authors classified 79 patients who had a mean age (± SD) of 53.6 ± 13.6 years (range 30–78 years) into 4 groups according to the length of their follow-up. Patients in Group 1 were followed up for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…A recent study on the long-term outcomes of the OLD shows that the outcome deteriorates over time. Worsening of clinical outcome was correlated with radiologic degeneration at operated segment [ 7 ]. The discectomy causes a narrowing of the disc space, leading to an overloading of the facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the long-term outcomes of the OLD shows that the outcome deteriorates over time. Worsening of clinical outcome was correlated with radiologic degeneration at operated segment [ 7 ]. The discectomy causes a narrowing of the disc space, leading to an overloading of the facet joints.…”
Section: Discussionmentioning
confidence: 99%
“…Il-Nam et al proved in his study that included 79 patients operated upon by standard open discectomy for lumbar disk herniation that the VAS scores for back or leg pain and the ODI scores were low in the 1 st 10-year post-operative and increased slightly over time through the 15-20-year follow-up correlating with increase in radiological findings of spinal degeneration or instability. It has been suggested that these progressive degeneration in radiological findings make it more likely that clinical outcomes for these patients are the result of spinal degeneration [16].…”
Section: Patients May Experience Back Pain After An Open Lumbar Discementioning
confidence: 99%
“…Il-Nam et al found in his study marked improvement in the VAS score for the lower limb pain whom were operated for open lumbar discectomy over time, unlike the VAS score for the back pain that improved for 10 years and then started to worsen. However, it remains unclear whether worsening was due to spinal degeneration progressing with the natural aging process or was the result of accelerated degeneration after an OLD [16].…”
Section: Patients May Experience Back Pain After An Open Lumbar Discementioning
confidence: 99%
“…Traditional open lumbar microdiscectomy (OLM) is considered the gold standard of LDH treatment for its good efficacy in long-term follow-up 3 , 4 . In recent years, minimally invasive techniques have developed rapidly, and minimally invasive discectomy (MID) has been gradually applied to treat lumbar intervertebral disc herniation; this method is more minimally invasive and conducive to postoperative rehabilitation than open surgery 5 .…”
Section: Introductionmentioning
confidence: 99%